Staging a ‘Children’s Classic’, teaching racism: Pippi Longstocking ([2005] 2019) - Järvinen, Hanna (Intellect, 2024)
In 2019, the Finnish National Ballet company brought onstage the 2005 Royal Swedish Ballet production Pippi Longstocking, based on Astrid Lindgren’s works for children. This article uses the ballet production as an example of how intertextual contexts complicate choices made in representation, and how canonicity is used to shelter derivative works from criticism. The specific focus is on the compound effect of the choices made by the ballet’s creators to include aspects of Lindgren’s novels that have been criticized for racism by taking recourse to ballet’s own traditions of racist representation. The ballet adaptation draws attention to systemic whiteness in Nordic countries still struggling to acknowledge their histories of colonialism and racism. Simultaneously, the Finnish company’s decision to change the choreography in August 2022 reveals how even an art form as intimately linked with European colonialism as ballet needs to change with the times.
Keywords: baletti (taiteet); historia; tanssi; tanssijat; rasismi; esitykset; baletit (teokset)